The Changing Incidence of Geography - Anderson, James E; Yotov, Yoto V (American Economic Review, 2010)
The incidence of bilateral trade costs is calculated here using neglected properties of the structural gravity model, disaggregated by commodity and region, and re-aggregated into forms useful for economic geography. For Canada's provinces, 1992–2003, sellers' incidence is on average some five times higher than buyers' incidence. Sellers' incidence falls over time due to specialization, despite constant gravity coefficients. This previously unrecognized globalizing force drives big reductions in “constructed home bias,” the disproportionate predicted share of local trade; and large but varying gains in real GDP. (JEL F11, F14, R12)